2005
DOI: 10.1007/s00330-005-2870-2
|View full text |Cite
|
Sign up to set email alerts
|

MR-guided biopsies of lesions in the retroperitoneal space: technique and results

Abstract: The purpose of this study was to evaluate the safety and precision of MRI-guided biopsies of retroperitoneal space-occupying tumors in an open low-field system. In 30 patients with indistinct retroperitoneal tumors [paraaortic lesion (n=20), kidney (n=2), suprarenal gland (n=3) and pancreas (n=5)] MR-guided biopsies were performed using a low-field system (0.2 T, Magnetom Concerto, Siemens, Germany). For the monitoring of the biopsies T1-weighted FLASH sequences (TR/TE=160/5 ms; 90 degrees ) were used in all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 31 publications
(50 reference statements)
0
18
1
Order By: Relevance
“…The sensitivity of 95.5% in our series is superior to the results from previous studies [6,[11][12][13], where a range of 75-94% has been reported. Although our data are based on only 25 patients, it seems reasonable that the usage of a wide-bore high-field MR machine improves biopsy results.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The sensitivity of 95.5% in our series is superior to the results from previous studies [6,[11][12][13], where a range of 75-94% has been reported. Although our data are based on only 25 patients, it seems reasonable that the usage of a wide-bore high-field MR machine improves biopsy results.…”
Section: Discussioncontrasting
confidence: 56%
“…Their titanium alloys are generally softer; therefore, the overall needle performance is inferior to normal stainless steel needles [5,16,21]. We found that, especially in cirrhosis, the needle movement inside the liver does not follow the examiners manoeuvres outside the patient.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…All facet joint injections were performed as outpatient procedures without premedication at a C-shaped open 0.2-T MR imaging system (Magnetom Concerto, Siemens Medical Solutions, Erlangen, Germany) equipped with a vertically oriented static magnet field (B 0 ) [13][14][15]. A flexible single loop body coil with a diameter of 45 cm was used.…”
Section: Methodsmentioning
confidence: 99%
“…Different imaging methods, with specific advantages and disadvantages, such as ultrasound (US), Xray fluoroscopy, CT and MRI, have been used to guide the interventions [1][2][3][4][5][6][7][8]. MR imaging has proven to be accurate as a guiding method in performing biopsies for a variety of indications [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%